Some notes about the books of Žygimantas Augustas in the Vilnius University Library - Braziūnienė, Alma (Knygotyra, 1997)
The article deals with the fate of the famous book collection of Sigismundus Augustus (1520-1572), Lithuanian Grand Duke and King of Poland. The private library of Sigismundus Augustus was a typical Renaissance library, comprising remarkable books on medicine, law, philosophy, literature, etc. It differed from other court libraries in Europe, which usually followed family traditions. An estimate of this wonderful collection was between 4,000 and 5,000 volumes. According to the will of Sigismundus Augustus, his book treasures were to be donated to the Jesuits College in Vilnius (i.e., Vilnius University), but his wish was only partially fulfilled. The majority of this collection was dispersed and partly destroyed during wars and other calamities. At present, the Library of Vilnius University possesses only 14 volumes (20 titles) from this collection. The majority of the dispersed books with provenance inscriptions from the Vilnius Jesuits College (68 volumes) are in the Library of the Academy of Sciences in St. Petersburg.The review of the provenance of the surviving royal collection in the Library of Vilnius University and some notes concerning the questionable cases of provenance are presented in this article.
Keywords: -